Does tourist generated content (TGC) boost tourist motivation better? Dual verification via ISM-DEMATEL approach and experimental study(旅游者照片更能提升人们的旅游意愿吗？) - 张若愚(ZHANG Ruoyu); 张高军(ZHANG Gaojun); 蒋婧怡(JIANG Jingyi); 程泷(CHENG Long) (Zhejiang Daxue xuebao. Lixue ban, 2024)
Among a plethora of destination marketing and traveler comparative studies, an integral theoretical supposition is that public information uploaded by travelers such as narratives and photographs possess greater potential to catalyze travel intention. However, this hypothesis remains unsubstaintiated through empirical research. To this end, this paper takes tourism photos as the starting point, adopts the idea of cross-examination to seek the stability of the research conclusions, constructs an index system of the influence of tourism photos on tourism willingness in three dimensions of "express" factors, "hints" factors and information quality, and introduces the ISM-DEMATEL method to construct an explanatory structure model. The robustness of the ISM-DEMATEL results are verified by experimental studies. Our study found that: Firstly, the hierarchical model of tourism photos affecting travel willingness has four levels, and the authenticity of information occupies the most significant position; Secondly, the level of typical characteristics of tourist generated content (TGC) is generally higher than that of official generated content (OGC), that is, in the process of stimulating people's willingness to travel, TGC are higher importance. Thirdly, the experimental results show that photos can significantly improve people's willingness to travel, which confirms that travel photos are a good destination marketing medium, and the promotion effect of TGC is the strongest among the three types, followed by the common feature of OGC and TGC, and finally the feature of OGC. At the theoretical level, this paper confirms the importance of TGC compared with OGC to tourism marketing, and consolidates the theoretical basis of related research; In practice, this paper argues that more focus should be attached on the quality of information in tourist photos and appropriately draw on the style of TGC to build a more attractive destination image.(在大量的目的地营销机构和旅游者比较研究中，一个重要的理论假设是旅游者上传的公开信息，如文案、照片，更能激发人们的旅游意愿，但此假设未经实证研究证实。为验证此假设，首先构建旅游照片影响旅游意愿的指标体系，包括明示、暗示、信息质量三类共18个因素，引入基于专家打分的集成解释结构模型-决策实验室分析（ISM-DEMATEL）方法构建解释结构模型，将照片对旅游意愿的影响分为4个层级，其中最重要的是真实性，而具有旅游者生成内容（tourist generated content，TGC）典型特征的因素层级普遍高于具有官方生成内容（official generated content，OGC）典型特征的，TGC对旅游意愿的刺激作用更大。然后，设计了对照实验，以潜在旅游者为被试，检测三类照片对旅游意愿的影响情况，交叉检验有利于进一步提高研究结果的稳健性，得到了相似的结果，即生成内容能够显著提高人们的旅游意愿，其中具有TGC典型特征的照片提升效果最好，其次是具有OGC和TGC共同特征的照片，最后是具有OGC典型特征的照片。在理论层面，从专家和旅游者的角度通过量化关系回答了为什么TGC对旅游意愿的吸引力较OGC强；在实践层面，提出目的地营销机构应重点关注TGC的信息质量，并适当借鉴TGC的形式与风格，在保持官方特色的基础上贴近旅游者。)